Myths and traditions of Huarochiri during the seventeenth century - Vasquez Monge, Eduardo (2011)
In (he sixreenth cenrury, Spanish priesrs ro evangelízc the narives of rhe central Andes who ehereafier were considcred Christians, but despite che efforrs of priesrs the narive, whom rhe Spanish called «indigenous», persisted in their beliefs religíous. Francisco de Avila, docrrinaire priesr of Sr, Damian, Huarochiri, recollectcd informacion from rhcse beliefs in Huarochirí and dcnounccd rhis «idoíarry» ro play an irnporrant role in che firsr season of «cxrirpation of idolatry». lhis documenr now known as che QUi'chullManuscript Huarochiri was onc of rhe docurnenrs this process of «exrirparion uf idolatry» and his study provides us such tites and religious rradirions no longer existo Eradicarion campaigns rried ro eliminare rhe persistcnce of «ídolatry- among Indians, for the prlcsrs rhe dcvil appeared as a ciernon tllnny, a succubus, which penerrared rhrough the drcarns, identified wírh rhe «supay- who possessed idols.